Flexural response of a continental margin to sedimentary loading and lithospheric rupturing: The mountain ridge between the Levant Basin and the Dead Sea Transform. Issue 2 (25th February 2014) - Steinberg, J.; Gvirtzman, Z.; Garfunkel, Z.
Abstract During the past 37 Myr the Levant Basin subsided under a 6 km sedimentary section while the adjacent area, Israel's mountainous backbone (Judea Hills), emerged to an elevation of ~1 km above sea level. What was the flexural contribution of offshore loading to the inland uplift that was also affected at that time by widespread geodynamic heating and uplifting? This question becomes particularly challenging considering that in the middle of this period the lithosphere adjacent to the basin (100–200 km east) ruptured and a new plate boundary was formed along the Dead Sea Transform (DST). How did this influence the strength of the lithosphere, and how did it change the shape of the flexure? We model the flexure caused by offshore sedimentary loading in two phases. The pre‐DST phase applies a flexural solution for an elastic plate without lithospheric rupturing (infinite boundaries). The post‐DST phase applies a flexural solution of an elastic plate with a free edge, set to resemble a lithosphere with no friction, and free to move vertically. The apparently unrealistic free edge simplification for a plate boundary provides an upper limit for the uplift. It is shown that before the initiation of the DST the flexural effect of the offshore loading on the inland region was negligible, and thus, most of the observed inland uplift should be explained in terms of deep‐seated tectonic processes. On the contrary, the last phase of uplift postdating the formation of the DST was influenced by flexural loading offshore that was intensified near the plate edge.